Estrategias de fiscalización tributaria aplicadas para la recaudación del impuesto predial en la Municipalidad Provincial Sánchez Carrión, 2021-2022 - Mauricio Villanueva, Dionicio Alex (2022)
The main objective of this professional sufficiency report is to propose a tax control strategies to improve the collection of property tax in the Municipality of Sánchez Carrión, 2022. For this, an analysis of the main problems that arise in the entity under study was carried out, obtaining that there is a low level of property tax collection in recent years, there are distortions in the patterns of use and occupation of urban land, outdated municipal cadastre, lack of training for the personnel in charge of municipal revenues, and low tax culture of citizens. Given this, an alternative solution has been carried out, consisting of applying control strategies, in order to contribute to greater collection. Regarding the analysis of the study plan that I carried out during the years of study of the Administration career, it can be said that it was a quality and enriching education to confront the labor market, however there are also weaknesses that must be improved as signed more alliances with companies so that the student develops his practices or collaborates with the operation of the same; as well as it is essential to provide updated knowledge and work on real Peruvian cases, whether national or local.